2000
DOI: 10.4049/jimmunol.164.4.1889
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Bovine MHC Class I-Like Fc Receptor

Abstract: In the cow, maternal immunity is exclusively mediated by colostral Igs, but the receptor responsible for the IgG transport has not yet been identified. The role of an IgG-Fc receptor (FcRn) that resembles a class I MHC Ag in transporting IgGs through epithelial cells was recently shown in selected species. We now report the cloning and characterization of the bovine FcRn (bFcRn). The cDNA and deduced amino acid sequences show high similarity to the FcRn in other species, and it consists of three extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 61 publications
4
84
0
3
Order By: Relevance
“…The Fc-binding FcRn is a heterodimer, which comprises ␤ 2 -microglobulin and a membrane-anchored ␣ chain that is related to the ␣ chain of major histocompatibility complex class I molecules. The corresponding sequences and overall structures are well conserved across species such as in human, mouse, rat, and cow (2,3,4,5,6,7), as well as in non-eutherian mammals (8). However, differences in their binding specificity to various IgG exist (9), indicating the presence of species-specific binding mechanisms.…”
Section: Conclusive Evidence Indicates That the Neonatal Fc Receptor mentioning
confidence: 99%
“…The Fc-binding FcRn is a heterodimer, which comprises ␤ 2 -microglobulin and a membrane-anchored ␣ chain that is related to the ␣ chain of major histocompatibility complex class I molecules. The corresponding sequences and overall structures are well conserved across species such as in human, mouse, rat, and cow (2,3,4,5,6,7), as well as in non-eutherian mammals (8). However, differences in their binding specificity to various IgG exist (9), indicating the presence of species-specific binding mechanisms.…”
Section: Conclusive Evidence Indicates That the Neonatal Fc Receptor mentioning
confidence: 99%
“…Evidence derived in ruminants is in favour of the hypothesis that FcRn selectively transports IgG from serum to milk. [14][15][16][17] Previous studies have shown that expression of the Fc receptor in the mammary gland correlates with the period of highest IgG-transfer into milk in three species: possum, sheep and pigs. 15,18,19 However, the data obtained from rodent models supports the notion either that FcRn was not involved in IgG transfer from serum to milk or that transport of IgG was in an inverse correlation with their binding affinity to FcRn.…”
Section: Introductionmentioning
confidence: 99%
“…and Thompson-Crispi et al (2013) found similar results, in milk and plasma respectively. The present findings showed that NAb levels were lower in milk than in plasma, this is in agreement with earlier studies NAb isotypes IgM and IgG may both be transported from plasma to milk (Kacskovics et al, 2000; in varying degrees depending on stage of lactation, colostrogenesis, and also in response to inflammation in the mammary gland. Phenotypic correlations between NAb levels measured in plasma and milk were moderately positive (Table 2.4), which means that these correlations are not close to one and are lower than genetic correlations.…”
Section: Phenotypic Parameters Of Nab Levels In Milk and Plasmasupporting
confidence: 81%